DEIXIS IN THE CLEVER SERVANT STORY - Liawati, Azizah; Rizkiani, Siska; Jamaludin, Agil (IKIP Siliwangi, 2020)
Pragmatics is a study of contextual meaning. Finding out the context and meaning of a conversation can be learned through deixis. This research analyzes types of deixis such as personal, time and place deixis. This research discusing about recount text entitled